On the molecular taxonomy of the Dendrobaena alpina species complex, with description of a new species (Crassiclitellata, Lumbricidae) - Csuzdi, Csaba; Valchovski, Hristo; Krízsik, Virág; Pavlíček, Tomáš; Szederjesi, Tímea (Zootaxa, 2023)
The molecular phylogenetic analysis of the D. alpina species group and related taxa revealed that this group in the present form is polyphyletic. The dark-red pigmented D. alpina alpina (Rosa, 1884) specimens from the Alps form a distinct clade together with D. alpina alteclitellata (Pop, 1938) and D. clujensis Pop, 1938 (Central European clade). The unpigmented Bulgarian specimens are now part of a clade consisting of Anatolian and Levantine species, namely D. orientalis Černosvitov, 1940, D. pentheri (Rosa, 1905), D. orientaloides Zicsi, 1985 and D. semitica Rosa, 1893a. Consequently, the unpigmented worms from Bulgaria represent a new species described herein as Dendrobaena misirlioglui sp. nov.